Green Synthesis of Silver Nanoparticles with Glucose for Conductivity Enhancement of Conductive Ink - Qifeng Chen; Guhong Liu; Guangxue Chen; Ting Mi; Jinglei Tai (BioResources, 2016)
This work reported a green method of synthesizing silver nanoparticles (AgNPs) with glucose acting as reducing agents to improve the conductivity of conductive ink. Silver nitrate, glucose, and polyvinylpyrrolidone (PVP), were used as silver precursor, reducing agent, and capping agent, respectively. The optimal condition of synthesizing AgNPs was obtained by varying the reactant ratio and temperature. The AgNPs were characterized by X-ray diffraction (XRD), UV-visible spectroscopy (UV-Vis), and scanning electron microscope (SEM). The obtained AgNPs with diameters of 80 to 100 nm were almost spherical and they were redispersed well in polyurethane acrylate (PUA). Compared with traditional hydrazine hydrate, the prepared AgNPs were better with respect to uniform size, dispersion, stability, and the absence residual solvent. After UV sintering, the conductivity (2.3×105 S/m) and mechanical properties of prepared conductive ink were good. Therefore, using glucose as a reducing agent to prepare AgNPs conductive ink is feasible and noteworthy because it is an extremely common material.